Stories of Origins in the Athena Parthenos: Iconology of Erechtheus and Pandora - Abramovich, Lorena Valeria (Eikón / Imago, 2016)
: In the Chryselephantine statue of the Parthenon two stories about the origins were symbolized: The first one was the beginning of the sexed humanity, represented by Pandora; the other story refers to the origin of the Athenian genos. The inclusion of the chthonic serpent had an intimate connection with the iconographic program of the Parthenon, a monument that celebrated the civic values and vernacular myths. However, the introduction of Pandora refers to broader Hellenic traditions, posing a more problematic question to be elucidated within this context. We postulate that the figure of Pandora is related to the myths of autochthony, and that she represents a counterimage of this Athenian claim. Pandora personifies the mythical origins of mankind, and Athenians separate themselves from this breed by appealing to the myth of Erechtheus, therefore they can build a different and superior genos. Athens rises from the very beginning, right from Erechtheus, above the line of Pandora.